Peran Mahasiswa Kuliah Kerja Nyata dalam “Membangun Kesadaran Stop Bullying and Start Caring melalui Edukasi Anti Bullying, Sehat Bersama, Cerdas Minum Obat dan Gizi Seimbang” di SDN Cijanggel Desa Kertawangi Kecamatan Cisarua: Pengabdian - Azahra Naqqiyyah Dianti; Miftahul Huda; Daniya Zain Aiman; Dewo Nugroho Yoga Pangestu; Dinda Nabila; Furqon Nurwahid; Putri Nurlathiifah Sudarli; Regina Supartini; Shanilla Nuzullul Rahmi; Thalita Salsabila; Yosef Cindi Septian (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Community Service Program (KKN) is a form of student community service as part of the implementation of the Tri Dharma of Higher Education. The KKN activity by Group 5 of the University of Muhammadiyah Bandung was conducted at Cijanggel Elementary School, Kertawangi Village, Cisarua District, with the aim of raising student awareness regarding the importance of bullying prevention, proper medication use, and providing balanced nutrition. The methods used included school condition surveys, observations, interviews, and educational approaches through games, discussions, and interactive media. The results showed that students had a better understanding of the negative impacts of bullying, were able to identify behaviors that constitute bullying, and had a better understanding of the importance of maintaining health through balanced nutrition and proper medication use. This KKN program contributes to creating a safe and healthy school environment that supports optimal child growth and development.